A non-invasive PC-based measurement of fetal phonocardiography - Moghavvemi, M.; Tan, B.H.; Tan, S.Y. (Elsevier, 2013)
A simple, low cost and non-invasive PC-based system that is capable to process real time fetal phonocardiographic signal has been built. The hardware of the system mainly consists of two modules: the front-end module and the data acquisition & control module. The front-end module is mainly used for heart sound signal capturing and conditioning. A new electronic stethoscope with enhanced performance that is non-intrusive, cost friendly and simple to implement has been built. The audio output unit enables the system to provide simultaneous listening and visual representation of the heart sound. The data acquisition & control module offers a four-channel analog multiplexer, a programmable gain amplifier, and a 12-bit resolution ADC. Various sampling rates can be provided through the programmable timer. Window 95-based software, which processes the real time heart sound signal, has been developed. The software written for the PCG allows for both time varying amplitude graph and power spectral plot (based on 512-point fast Fourier transform (FFT)) to be shown simultaneously on a channel's view. The simultaneous spectrograms gives a much better insight of the heart sounds characteristics than just the time-amplitude plot alone as in conventional PCG software. Using digital signal processing techniques, the power of the spectral plot is used to extract useful information of the heart sounds characteristics even in a situation where the heart sounds are among considerably loud background noises.